2013
DOI: 10.1364/ol.38.001685
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dot rolled-up microtube optoelectronic integrated circuit

Abstract: A rolled-up microtube optoelectronic integrated circuit operating as a phototransceiver is demonstrated. The microtube is made of a InGaAs/GaAs strained bilayer with InAs self-organized quantum dots inserted in the GaAs layer. The phototransceiver consists of an optically pumped microtube laser and a microtube photoconductive detector connected by an a-Si/SiO2 waveguide. The loss in the waveguide and responsivity of the entire phototransceiver circuit are 7.96 dB/cm and 34 mA/W, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…[7][8][9][10] The tube waveguide has been demonstrated both theoretically and experimentally to support whispering gallery modes (WGM) circulating along its circumference. 6,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] The light can be evanescently coupled between the tube and a straight waveguide once their separation is made adequately small, typically within a fraction of the wavelength of the propagating light. Several research groups have already demonstrated 3D photonic integration using the tube waveguide.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10] The tube waveguide has been demonstrated both theoretically and experimentally to support whispering gallery modes (WGM) circulating along its circumference. 6,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] The light can be evanescently coupled between the tube and a straight waveguide once their separation is made adequately small, typically within a fraction of the wavelength of the propagating light. Several research groups have already demonstrated 3D photonic integration using the tube waveguide.…”
mentioning
confidence: 99%
“…Several research groups have already demonstrated 3D photonic integration using the tube waveguide. 11,20,24,26 However, a monolithically integrated version of the tube waveguide to a planar ridge waveguide coupling has not yet been demonstrated experimentally. The result we report here is a monolithically integrated resonator-based vertical photonic coupler on silicon platform.…”
mentioning
confidence: 99%
“…The performance of other 2D materials, such as 2D topological insulators [ 60 ] and 2D self‐crimping materials, [ 61 ] has also proved to be excellent in THz detection and 2D materials are likely to play an important role in the future. The diversity and excellent physical properties of 2D materials enable their significant advantages in THz detection.…”
Section: Core Materials and Devices In New Spectrum Communicationmentioning
confidence: 99%
“…By embedding active media (e.g., quantum dots and quantum wells) into one of the strained layers, microtubes can function as on-chip coherent light sources [6][7][8][9][10][11][12]. Other novel microtube-based PIC components, such as filters, modulators, directional couplers, and phototransceivers have also been realized [13][14][15]. The applications of microtubes are not limited to photonic integrated devices.…”
Section: Introductionmentioning
confidence: 99%